Molecular characterization and genetic diversity assessment of phytophthora isolates from various crops and soil using RAPD-PCR - Pahm, Scheherazaide Yoradyl Ampatuan (2008)
Genetic variations and relationships
Genetic variation and relationships of six Phytophthora isolates obtained from different hosts (avocado, cacao, coconut, durian fruit stem and soil) in Davao City were determined using RAPD technique. The five primers yielded 36 markers with a total of 65 bands. Fifty-nine of the bands were polymorphic (90%). Monomorphism was observed in 900 bp generated by P-02. Fragment sizes ranged from 307 to 1437 bp with the largest being generated by the coconut isolate in P-01 and the smallest by the soil isolate in P-10. Values for genetic distance ranged from 0.048141 to 0.283265. the isolates from durian fruit and stem established the smallest distance, while isolates from coconut and avocado, and avocado and soil showed the largest distance. The avocado isolate was the most distant from other five isolates. Clustering analyses revealed identical topologies with varying bootstrap values with the avocado isolate used a outgroup. The three phylogenetic trees depicted two lineages. The first was composed of cacao and soil isolates, while the second contained isolates from coconut, durian fruit and durian stem. Grouping of Phytophthora from durian fruit and stem was consistently supported by high bootstrap values from Fitch (83%), neighbor joining (89%), and UPGMA (99%). Phylogenies generated from morphological data supported the clustering of isolates from durian with bootstrap values of 78% for Fitch and 79% for UPGMA. Dendograms from the combination of molecular and morphological traits further supported that the durian isolates were closely related with strong bootstrap values of 90% from Fitch, 96% from neighbor joining, and 100% from UPGMA. In all analyses, collapsing the nodes with weak bootstrap support revealed the same topologies; where durian fruit and stem isolates clustered, while isolates from soil, coconut, cacao, and avocado each formed separate lineages. Results showed that variations in the morphology of the six isolates were detected at the genetic level, that isolates obtained from durian are closely related, and that the other four isolates; avocado, cacao, coconut, and soil produced their own distinct clusters
Thesis (BS Biology) -- University of the Philippines Mindanao, 2008
Keywords: Fitch; Neighbor joining; Phytophthora isolates; Phytophtora cultures